State‐of‐Play and Emerging Challenges in Photovoltaic Energy Yield Simulations: A Multi‐Case Multi‐Model Benchmarking Study. Issue 8 (15th November 2022) - Tsanakas, Ioannis (John) A.; Lokhat, Ismaël; Jay, Arnaud; Gregoire, Clément; Schnierer, Branislav; Rusnak, Jozef; Dvonc, Lukas; Berthelot, Joséphine; Monet, Chloé; Garcia, Kévin; Lombardero, Iván; Leloux, Jonathan; et al.
Abstract : In the framework of the H2020 SERENDI‐PV project, it is aspired to tackle challenges in photovoltaic (PV) modeling and yield simulations, that are emerging today, on four interrelated aspects: i) improved modeling of loss/degradation mechanisms, ii) improved modeling of bifacial PV, floating PV, and building integrated photovoltaics systems, iii) solar resource and uncertainties modeling, and iv) financial risks modeling. As groundwork for this effort, a comprehensive 8‐month study is carried out, the results of which are presented in this article. The study has two parts and main objectives: i) a comprehensive survey addressed to multiple stakeholders, to identify and assess today's "best practices" and needs of the PV industry on PV energy yield simulations; ii) a multi‐model multi‐case benchmarking and evaluation study, i.e., of eight state‐of‐the‐art tools/software for PV energy yield simulations of seven real‐life PV systems addressing diverse "scenarios" (different climates, site characteristics, PV typologies, and technologies). Abstract : This article presents key results of a study with a twofold objective: i) a comprehensive survey addressed to multiple stakeholders, to identify/assess today's "best practices" and needs of the photovoltaics industry on energy yield simulations; ii) a multi‐model multi‐case benchmarking study of eight state‐of‐the‐art tools/software for energy yield simulations for seven real‐life photovoltaic systems "scenarios" (different climates, site characteristics, typologies, technologies).